2017
DOI: 10.18203/2349-2902.isj20175893
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of RIPASA score in the diagnosis of acute appendicitis

Abstract: Background: Acute appendicitis is one of the most common surgical emergencies. Despite being a common problem, it remains a difficult diagnosis to establish, particularly among the young, the elderly and females of reproductive age. The study aimed to compare the efficacy of RIPASA score in the diagnosis of acute appendicitis.Methods: In this cross sectional comparative study, 100 cases of pain in the right iliac fossa were admitted and evaluated clinically. RIPASA score was calculated for all. Ultrasound (USG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Nanjundaiah N et al, also demonstrated that the sensitivity of the RIPASA scoring system was higher than that of the Alvarado scoring system for the diagnosis of acute appendicitis, i.e., 96.2% and 58.9%, respectively [22]. According to Karapolat B, the RIPASA scoring system can accurately diagnose acute appendicitis, including the pathological stage, without the use of computed tomography [23]. Bhatnagar SP and Chavan S proved that RIPASA is more efficient [24].…”
Section: Discussionmentioning
confidence: 99%
“…Nanjundaiah N et al, also demonstrated that the sensitivity of the RIPASA scoring system was higher than that of the Alvarado scoring system for the diagnosis of acute appendicitis, i.e., 96.2% and 58.9%, respectively [22]. According to Karapolat B, the RIPASA scoring system can accurately diagnose acute appendicitis, including the pathological stage, without the use of computed tomography [23]. Bhatnagar SP and Chavan S proved that RIPASA is more efficient [24].…”
Section: Discussionmentioning
confidence: 99%
“…Nanjundaiah N et al, also demonstrated that the sensitivity of the RIPASA scoring system was higher than that of the Alvarado scoring system for the diagnosis of acute appendicitis, i.e., 96.2% and 58.9%, respectively [22]. According to Karapolat B, the RIPASA scoring system can accurately diagnose acute appendicitis, including the pathological stage, without the use of computed tomography [23]. Bhatnagar SP and Chavan S proved that RIPASA is more efficient [24].…”
Section: Discussionmentioning
confidence: 99%
“…These results emphasize again that a positive ultrasonography for appendicitis is in favthis of a diagnosis of acute appendicitis. However, a negative ultrasound is not sufficient to rule out the diagnosis of acute appendicitis [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Acute appendicitis is one of the most common surgical emergencies encountered in the world particularly among the young adults and children [1]. Surgeon's good clinical assessment is considered to be the most important requisite in the diagnosis of appendicitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation